2018
DOI: 10.1186/s12886-018-0907-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel surgical technique for prevention of Ahmed glaucoma valve tube exposure: long scleral flap augmented with Tenon advancement and duplication

Abstract: BackgroundTo describe a new technique and present its long-term outcome for prevention of Ahmed glaucoma valve (AGV) tube exposure in patients with refractory glaucoma.MethodsTwenty-seven eyes of 24 patients (mean age, 50 years; age range, 16–78 years; 8 females, 16 males) with refractory glaucoma who had the AGV implant were retrospectively reviewed. For AGV implantation, a long scleral flap combined with Tenon advancement and duplication was used. In this technique, a long scleral flap is created to complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
2
Order By: Relevance
“…The lack of long-term outcomes and small sample sizes were pervasive among retrospective cohort studies without patch grafts (Supplemental Digital Content 2, http://links.lww.com/IJG/A796). The 5 graft-free studies identified had variable surgical techniques, including scleral tunnels and flaps 7–11 . None reached 5 years of follow-up, with only Gdih and Jiang 7 reporting success rate at 1 year, which was lower than ours (87% vs. 91%).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The lack of long-term outcomes and small sample sizes were pervasive among retrospective cohort studies without patch grafts (Supplemental Digital Content 2, http://links.lww.com/IJG/A796). The 5 graft-free studies identified had variable surgical techniques, including scleral tunnels and flaps 7–11 . None reached 5 years of follow-up, with only Gdih and Jiang 7 reporting success rate at 1 year, which was lower than ours (87% vs. 91%).…”
Section: Discussioncontrasting
confidence: 58%
“…Supplemental Digital Content 2, http://links.lww.com/IJG/ A796 shows the result of a literature review comparing the current study to others with at least 1 year of follow-up after AGV implantation. 2,3,5,[7][8][9][10][11][12][13][14][15][16] The current study reported numerically higher rates of success at all time points compared with all retrospective cohort studies with patch graft usage except for one 15 (Supplemental Digital Content 2, http://links.lww.com/ IJG/A796). These studies included at maximum 58 eyes, using different types of patch grafts (dura, scleral, and pericardial).…”
Section: Success Ratesmentioning
confidence: 89%
See 1 more Smart Citation
“…[ 5 ] Comparative series of graft free scleral tunnel versus scleral patch graft by Rivera et al [ 6 ] and Pakravan et al [ 7 ] reported tube erosions in the later, but not in former group of patients. Alternate techniques like use of 6-mm graft free scleral tunnel,[ 8 ] needle-generated scleral tunnel, without a tube-covering patch[ 9 ] and long scleral flap, augmented with Tenon advancement and duplication[ 10 ] have also been described in literature.…”
Section: Discussionmentioning
confidence: 99%
“…This will ensure optimum utilization of scarcely available donor cornea and will also drive down costs. Some surgeons avoid the use of a PG altogether, either by creating a long tunnel[ 2 ] or by entering the anterior chamber (AC)/sulcus under a long scleral flap[ 3 ] or even by combining the tunnel and the flap. [ 4 ]…”
mentioning
confidence: 99%